Comparison of different antibiotic regimes for preventive tooth extractions in patients with antiresorptive intake: a retrospective cohort study - Ristow, Oliver; Rückschloß, Thomas; Schnug, Gregor; Moratin, Julius; Bleymehl, Moritz; Zittel, Sven; Pilz, Maximilian; Sekundo, Caroline; Mertens, Christian; Engel, Michael; Hoffmann, Jürgen; Smielowski, Maximilian (Antibiotics, 2023)
In the present study, the impacts on success rates between three different antibiotic regimes in patients receiving preventive tooth extraction during/after antiresorptive treatment were compared. For the retrospective analysis, we enrolled patients who had undergone tooth extraction from 2009 to 2019 according to the specified preventive conditions under antiresorptive therapy. Three antibiotic regimens were distinguished: (Group 1) intravenous for 7 days, (Group 2) oral for 14 days, and (Group 3) oral for 7 days of application. The primary endpoint was the occurrence of medication-related osteonecrosis of the jaw at 12 weeks after surgery. A total of 760 patients and 1143 extraction regions were evaluated (Group 1 n = 719; Group 2 n = 126; Group 3 n = 298). The primary endpoint showed no significant difference in the development of medication-related osteonecrosis of the jaw between the groups studied (Group 1 n = 50/669 (7%); Group 2 n = 9/117 (7%); Group 3 n = 17/281 (6%); p = 0.746). Overall, the success rate was 93% after intervention when preventive measures were followed. With the same success rate, a reduced, oral administration of antibiotics seems to be sufficient regarding the possible spectrum of side effects, the development of resistance and the health economic point of view.
Gesehen am 16.08.2023